A contribution to a virtual enterprise taxonomy - Putnik, G. D. (2014)
This paper presents a taxonomy able to contribute to building a framework within the domain of Virtual Enterprises (VE). A VE taxonomy currently does not exist, and this lack is felt in the ambiguous way that some concepts are addressed, leading to a fragment understanding that hinders the development of the science of VE integration and management. The structure of the taxonomy developed is based on the view of the system as a 5-tuple consisting of Input, Control, Output, Mechanism, and Process, which is the underlying system-view in the well-know IDEF0 diagramming technique. In particular, this taxonomy addresses the VE extended lifecycle that implies the use of a meta-organization called Market of Resources, as an original contribution to the VE theory and practice. The taxonomy presented is constructed in a way to be easily complemented with other VE partial taxonomies that may be found in literature.